Canadian Association of Radiologists Guidance on Contrast Associated Acute Kidney Injury. Issue 3 (August 2022) - Macdonald, D. Blair; Hurrell, Casey; Costa, Andreu F.; McInnes, Matthew D.F.; O'Malley, Martin E.; Barrett, Brendan; Brown, Pierre Antoine; Clark, Edward G.; Hadjivassiliou, Anastasia; Kirkpatrick, Iain D.C.; Rempel, Jeremy L.; Jeon, Paul M.; et al.
Iodinated contrast media (ICM) is one of the most frequently administered pharmaceuticals. In Canada, over 5.4 million computed tomography (CT) examinations were performed in 2019, of which 50% were contrast enhanced. Acute kidney injury (AKI) occurring after ICM administration was historically considered a common iatrogenic complication which was managed by screening patients, prophylactic strategies, and follow up evaluation of renal function. The Canadian Association of Radiologists (CAR) initially published guidelines on the prevention of contrast induced nephropathy in 2007, with an update in 2012. However, new developments in the field have led to the availability of safer contrast agents and changes in clinical practice, prompting a complete revision of the earlier recommendations. This revised guidance document was developed by a multidisciplinary CAR Working Group of radiologists and nephrologists, and summarizes changes in practice related to contrast administration, screening, and risk stratification since the last guideline. It reviews the scientific evidence for contrast associated AKI and provides consensus-based recommendations for its prevention and management in the Canadian healthcare context. This article is a joint publication in the Canadian Association of Radiologists Journal and Canadian Journal of Kidney Health and Disease, intended to inform both communities of practice.